The effects of sleep extension on physical and cognitive performance in AROTC cadets - Wedderburn, J'Michael, author; Broussard, Josiane, advisor; Lipsey, Tiffany, committee member; Eakman, Aaron, committee member; Brager, Allison, committee member (Colorado State University. Libraries, 2023)
College students and military personnel have limited sleep opportunities; Reserve Officer Training Corps (ROTC) cadets belong to both groups. Thus, cadets are at a heightened risk of insufficient sleep. Sleep loss can have deleterious effects on physical and cognitive health (Halson et al., 2014). In military professions, these impairments have potentially fatal consequences, as decreased performance will result in diminished operational readiness. Recent evidence suggests that sleep extension is a valid intervention to increase sleep duration (Bonnar et al., 2018). Thus, we aim to identify if sleep extension improves performance in chronically sleep-deprived ROTC cadets. This study examines the impact of 1-week of sleep extension on physical and cognitive performance in Army ROTC cadets. We recruited 16 healthy, active male and female participants aged 18-35 from Colorado State University's ROTC program. Participants were equipped with Actiwatches and completed daily sleep questionnaires and diaries during the habitual and sleep extension periods. Sleep extension was achieved by asking participants to spend 10 hours in bed to increase sleep by at least 1 hour per night. Cadets then completed a series of physical and cognitive tests to measure performance on tactically relevant tasks. The physical testing consisted of a vertical jump, 3-repetition maximal hexagon deadlift, 300-meter shuttle, and a 1-mile run; and cognitive test consisted of a psychomotor vigilance test, the Purdue pegboard test Tiffin (1948), the STROOP color-word test Jensen (1965), and a simulated shooting exercise. Wilcoxon Signed rank-test and two samples paired t-test statistical analysis compared baseline, physical, and cognitive testing data to post-intervention testing data. Cognitive and physical testing occurred after 1-week of habitual sleep and 1-week of sleep extension. The mean objective Total Sleep Time (TST) was 6.07 ± 0.15 hours during the baseline period and 7.03 ± 0.17 hours during the sleep extension period (P=<0.0001). The mean Epworth Sleepiness Scale (ESS) rating was outside of normal limits at 10.47 ± 1.16 during the habitual sleep period; it decreased to fall within the normal limits during the sleep extension period at 7.10 ± 0.79 (P <0.005) (Shattuck & Matsangas. 2014). There were statistically significant differences found on 2 of the 4 Purdue pegboard tests and deadlift performance from habitual sleep to the sleep extension period. The mean hands and assembly scores significantly improved (P = 0.038 and P=0.003, respectively). Performance on the 3-repetition maximal hexagon deadlift increased significantly during the habitual sleep period and sleep extension period (p = .007). The limited sleep opportunities ROTC cadets encounter have negative implications on physical and cognitive performance; based on our findings in the current study, it is plausible that sleep was not extended to an adequate duration to elicit cognitive and physical performance improvements in all of the tested cognitive and physical measure. Thus, more research is needed to investigate the relationship between sleep duration and sleep quality and their effect on cognitive and physical performance in tactical population.
Keywords: cognitive performance; sleep; tactical; physical performance; Army Reserve Officer Training Corps; sleep extension